Troxerutin Exerts Anti-Pulmonary Fibrosis Activity in Nicotine-Induced Lung Fibrosis on Zebra Fish Model - Yahya Hasan Hobani; Yahya Hasan Hobani
Cigarette smoking is the major obstacles to lung cell proteostatic imbalance due to the exposure of the respiratory epithelial cell to toxic oxidants. The most active ingredient presents in the cigarette smokers, nicotine causes number of health risk by synthesis of free radicals which alters the individual cell DNA stability. Troxerutin, a flavonoid derived from the Rutin, possess antioxidant potential which has been investigated for its anti-pulmonary fibrosis activity against nicotine associated inflammation in the gills of the Zebra fish. Objectives: The current study was carried out to analyse toxicity of nicotine in zebrafish model and the restoration of gill architecture by the action of troxerutin. Materials and Methods: The activity of troxerutin was investigated by evaluation of antioxidant levels, gene expression, and tissue architecture via histopathological studies of the nicotine-induced group. Results: Superoxide Dismutase (SOD) and Catalase (CAT) levels significantly decreased in the nicotine-induced group in our study than in the treated groups after the administration of Troxerutin. Myeloperoxidase (MPO), Nitrous Acid (NO), and Lipid Peroxidation (LPO) levels elevated in induced group which reduced significantly in Troxerutin-treated groups. It exerted protective effect by reducing the histopathological alterations linked to nicotine-induced group, enhancing antioxidant defence, modifying the oxidative status by scavenging free radicals and supressing inflammatory gene expression of IL-10, IL-1 gb (Bpro-inflammatory cytokine in Zebra fish model. Conclusion: The current study confirms the potential function of troxerutin in repairing nicotine-induced pulmonary fibrosis in the Zebrafish models